Respuesta :
Answer:
x=-8
Step-by-step explanation:
-4(2x+3) = 2x+6-(8x+2)
The first step is to distribute the -4 and the -1
-4*2x+-4*3 = 2x+6 -8x-2
-8x-12 = 2x+6-8x-2
Combine like terms
-8x-12 = -6x+4
Add 8x to each side
-8x+8x-12 = 8x-6x+4
-12 = 2x+4
Subtract 4 from each side
-12-4 = 2x+4-4
-16 = 2x
Divide by 2
-16/2 = 2x/2
-8=x
Answer:
[tex]x=-8[/tex]
Step-by-step explanation:
[tex]\mathrm{Expand\:}-4\left(2x+3\right):\quad -8x-12[/tex]
[tex]\mathrm{Expand\:}2x+6-\left(8x+2\right):\quad -6x+4[/tex][tex]-8x-12=-6x+4[/tex]
Add 12 to both sides:[tex]-8x-12+12=-6x+4+12[/tex]
→[tex]-8x=-6x+16[/tex]
Add 6x to both sides:[tex]-8x+6x=-6x+16+6x[/tex]
→[tex]-2x=16[/tex]
Divide both sides by -2:[tex]\frac{-2x}{-2}=\frac{16}{-2}[/tex]
Simplify.
Hope this helps!!